Art direction prospects in creation of modern content for domestic TV channels - Аlma Aidar, Мadina Bakeyeva; Omur, Songul; Toibayeva, Zhadyra; Bekniyazova, Saltanat (Opción, 2020)
This article studies the prospects for the development of digital broadcasting, terrestrial and digital portals, as well as indicates the specific role of art direction in the formation of a new direction in Kazakhstan. The article explores a new direction for broadcasting in Kazakhstan. The material for the study was the modern trends of digital and broadcasting. As a result, the development of television content, as well as forms of broadcasting in Kazakhstan, can be considered lagging. In conclusion, forms of broadcasting require research in this area and require the search for solutions from a scientific research point of view.